(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2016)
The 21 st century brought with it the commitment to face the development of societies in a complex and multidimensional way. The Human Development Approach opens new perspectives to fight for this commitment, which warrants a detailed and deep understanding of theories that open paths with more human directions and, therefore, allows the ethical approach to materialize the path. In this essay, an exercise in onceptual precision is made of what we consider to be a transdisciplinary field of knowledge on the subject of development; starting from the complex understanding of the processes, actors, relationships that define socio-political action for well-being. The evolution of ideas within the postmodernity framework must continue to address the changes that occur in the world under an interdependent conception of ecosystems. Humans are part of a system that overlaps us, and therefore we must respect the life of the planet. The, already irreversible, damage achieved by the modernizing pretensions must find a brake on an ideology that comprehends in a broad way the scheme of actions we design to complish our achievements. Today the quality of life must be understood from the precepts of ecohumanity.